Quality of life of parents, kidney donors or not, and biopsychosocial aspects of pediatric transplant - Hilgert, Cláudia; Rocha, Gibsi; Escosteguy, Norma; Coutinho, Márcia; Rios, Larissa Ferreira; Rios, Larissa Ferreira; Toffolo, Lauro; Kopittke, Martina Cezar; Mayer, Mayara; Luz, Vinicius Correa da; et al. (Brazilian Journal of Transplantation, 2009)
Purpose: To assess the quality of life of parents kidney donors or not, and biopsychosocial aspects involved in pediatric kidney transplantation. Methods: This is a cross-sectional study. The research was conducted with 31 parents of transplanted patients regularly monitored in a pediatric nephrology outpatient clinic. It was conducted individual interviews through questionnaires answered by donors and non-donor parents. The sample was composed by 61 parents, 15 donors and 46 non-donors, evaluated for 6 months. The subjects answered two questionnaires developed by the authors and the SF-36. Statistical analysis was performed on SPSS program. Statistical techniques consisted of contingency charts, chi-square test, Mann-Whitney test and Monte Carlo to attain the 5% significance chi-square. Results: The quality of life for donors and non donors showed the following averages in the 8 domains of the SF 36: physical function, 92/90; physical-role, 100/100, body pain, 72/72; general health, 89/82; vitality, 60/65; social function, 100/87; emotional-role, 100/100, and mental health, 68/68. There was no significant difference in the comparison between quality of life for donor and non-donor parents. Conclusion: There was no difference between quality of life of kidney donors and non donors, which does not exclude the need to set programs encouraging the living donation.